A genetic modifier suggests that endurance exercise exacerbates Huntington's disease. (2nd March 2018) - Corrochano, Silvia; Blanco, Gonzalo; Williams, Debbie; Wettstein, Jessica; Simon, Michelle; Kumar, Saumya; Moir, Lee; Agnew, Thomas; Stewart, Michelle; Landman, Allison; Kotiadis, Vassilios N; Duchen, Michael R; et al.
Abstract: Polyglutamine expansions in the huntingtin gene cause Huntington's disease (HD). Huntingtin is ubiquitously expressed, leading to pathological alterations also in peripheral organs. Variations in the length of the polyglutamine tract explain up to 70% of the age-at-onset variance, with the rest of the variance attributed to genetic and environmental modifiers. To identify novel disease modifiers, we performed an unbiased mutagenesis screen on an HD mouse model, identifying a mutation in the skeletal muscle voltage-gated sodium channel ( Scn4a, termed 'draggen' mutation) as a novel disease enhancer. Double mutant mice (HD; Scn4a Dgn/+ ) had decreased survival, weight loss and muscle atrophy. Expression patterns show that the main tissue affected is skeletal muscle. Intriguingly, muscles from HD; Scn4a Dgn/+ mice showed adaptive changes similar to those found in endurance exercise, including AMPK activation, fibre type switching and upregulation of mitochondrial biogenesis. Therefore, we evaluated the effects of endurance training on HD mice. Crucially, this training regime also led to detrimental effects on HD mice. Overall, these results reveal a novel role for skeletal muscle in modulating systemic HD pathogenesis, suggesting that some forms of physical exercise could be deleterious in neurodegeneration.